Implementation of Physical Education, Sports and Health Learning during the Covid-19 Pandemic at Senior High School (SMA) 1 Banyumas - Kartika Restiana, Dinar; Rahayu, Setya; Wahyudi, Agung (Journal of Physical Education and Sports, 2021)
The problem in this study is about learning that is carried out online due to the Covid-19 virus pandemic. This study aims to analyze implementing PESH learning during the pandemic. Then, analyzing what factors that can be the obstacles in implementing PESH learning during the pandemic. Besides, analyzing the supporting factors in the PESH learning process during the Covid-19 pandemic at SMAN 1 Banyumas. This research is a quantitative study. The samples were all physical education teachers at SMAN 1 Banyumas, and the amount is 3 physical education teachers and 50 students. The data collection techniques using observation, questionnaires, interviews, and documentation. The data analysis technique in this study used quantitative analysis with percentage data used to examine the variables in this study, namely the implementation of PESH learning during the Covid-19 pandemic. The results showed that the implementation of PESH learning during the Covid-19 pandemic at SMAN 1 Banyumas which included planning is 97%, implementation is 93%, evaluation is 96%. The obstacles in implementing PESH learning during the Covid-19 pandemic at SMAN 1 Banyumas is 31%. The supporting factor for implementing PESH learning during the Covid-19 pandemic at SMAN 1 Banyumas is 63%. The conclusion is that the implementation which includes planning, implementing and evaluating PESH learning during the Covid-19 pandemic at SMAN 1 Banyumas is very good. The obstacles of the implementation of PESH learning at SMAN 1 Banyumas are low. The supporting factor for implementing PESH learning during the Covid-19 pandemic at SMAN 1 Banyumas is in the good category.